P141 How accurate is clinical coding in recently integrated sexual health services?. (18th May 2015) - Umaipalan, Athavan; Parry, Laura; Kiritharan, Lalitha; Anderson, Heather; Sarner, Liat; Portman, Margaret
Abstract : Background/introduction: Clinical coding in England provides monitoring data for Public Health England via the Genitourinary Medicine Clinic Activity Dataset (GUMCAD) and Sexual and Reproductive Health Activity (SRHAD) returns. In London, this data is also used to reflect activity for the Integrated Sexual Health Tariff (ISHT) which may form the basis for payment in future. Integration of contraception and GUM services presents a challenge in maintaining accuracy of clinical coding. Aim(s)/objectives: To audit the accuracy of SHAPPT, SRHAD and SRH coding in a multi-site integrated sexual health service, comparing sites traditionally providing GUM services vs contraception. Methods: Local standards were agreed; 95% of patients should have accurate SHAPPT, SRHAD and SRH codes. 229 records from 2 GUM sites and 53 from 1 contraception site were audited from attendances between May and July 2014. Results: Discussion/conclusion: As expected, the accuracy of coding reflected the traditional nature of the sites. The locally set standard of 95% was only reached on one occasion. Missing SRH codes alone would equate to lost income of £1259 from 77 visits if the ISHT was in place. Staff training and weekly capture and correction of missing HIV codes through targeted email reminders has resulted in an improvement in coding.